Democratization, elections and the 'de facto state dilemma': Iraq's Kurdistan Regional Government. (December 2015) - MacQueen, Benjamin
De facto states are an anomalous, but well-discussed feature of international politics. The questions they raise for understandings of sovereignty and statehood are well advanced, but less understood are the internal dynamics of these entities particularly in relation to the development of democratic, participatory political institutions. Through an examination of the Kurdish Regional Government in Iraq from 1992 to 2014 this article will explore patterns of democratization in de facto states. Unpacking a dilemma around trends toward both exclusionary and inclusionary politics in de facto states, it is argued here that there is a positive relationship between de facto statehood and democratization. However, contrary to current views, this is the result of internal pressures and elite agency as opposed to normative pressures at the international level.